Experimental Practice Technoscience, Alterontologies, and More-Than-Social Movements - Papadopoulos, Dimitris (Duke University Press, 2018)
In Experimental Practice Dimitris Papadopoulos explores the potential for building new forms of political and social movements through the reconfiguration of the material conditions of existence. Rather than targeting existing institutions in demands for social justice, Papadopoulos calls for the creation of alternative ontologies of everyday life that would transform the meanings of politics and justice. Inextricably linked to technoscience, these "alterontologies"-which Papadopoulos examines in a variety of contexts, from AIDS activism and the financialization of life to hacker communities and neuroscience-form the basis of ways of life that would embrace the more-than-social interdependence of the human and nonhuman worlds. Speaking to a matrix of concerns about politics and justice, social movements, matter and ontology, everyday practice, technoscience, the production of knowledge, and the human and nonhuman, Papadopoulos suggests that the development of alterontologies would create more efficacious political and social organizing
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Sep 2020)
Keywords: SCIENCE / History; Discoveries in science -- Social aspects; Financialization -- Social aspects; Philosophical anthropology; Social movements; Technology -- Social aspects